KONSEP DASAR STRATEGI DAN METODE PEMBELAJARAN PAI DI SD/MI - Vera Yantika, Ade; Elsa Al Khansa; Muhammad Adib; Bagas Armayoga; Siti Zulaikhah; Imam Syafe’i (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The strategies and methods of Islamic Religious Education (PAI) learning in elementary schools (SD) and Islamic elementary schools (MI) play a crucial role in shaping students' character and religious knowledge. This study aims to explore the basic concepts of strategies and methods of PAI learning applied in SD and MI. The basic concepts of PAI learning strategies include approaches focused on the development of religious values, skills, and noble character. The methods used in learning should be adjusted to the students' needs, cognitive development, as well as their social and cultural environment. In PAI learning, effective interaction between teachers and students is expected through various methods, such as lectures, discussions, Q&A sessions, and religious practices. The selection of appropriate strategies and methods can enhance students' understanding of PAI material and strengthen the application of religious values in daily life.